Breast Cancer Awareness and Detection of Asymptomatic Cases Using Breast Palpation and Fine-needle Aspiration in Bafoussam, Cameroon - Richard, Tagne Simo; Ndopwang, Lydiane C.C.; Seke Etet, Paul F.; Nwabo Kamdje, Armel H.; Mohamadou, Halmata; Phelix Bruno, Telefo; Nangue, Charlette (Asian Pacific Journal of Cancer Care, 2020)
Background: Breast cancer, the deadliest cancer in women worldwide, is often diagnosed at late stage in Cameroon, with high mortality and dire socioeconomic consequences. We investigated the reasons for breast cancer late diagnosis in Cameroon. Methods: Women (412) were randomly recruited in various locations in the city of Bafoussam, West Region, Cameroon. They self-administered a questionnaire assessing breast cancer awareness. Then, they underwent breast palpation, followed by fine needle aspiration (FNA) when a nodule was found. Results: 65% of the study participants were above 30 years; 80.9% had at least a secondary education; 94.4% had heard about breast cancer and the main source of information was the media (57.3%). Most participants were either uninformed or ill-informed (up to 72%) about breast cancer risk factors, signs, and screening methods, in particular breast self-examination (BSE). Of the 17 women with nodules and other suspect signs, only 6 accepted fine needle aspiration (FNA). Three of the 6 had malignant nodules indicative of Invasive ductal carcinoma low grade (one case) and high grade (2 cases). Conclusions: Women living in Bafoussam are poorly aware of breast cancer screening methods, in particular BSE, and of the importance of early detection. BSE followed by FNA in women with nodules is a simple, yet good screening method to improve early detection and reduce the burden of breast cancer.